The Belgium artist of the gallery. (Gent : Richard Foncke Gallery)
Bekaert, Piet ; Bertrand, Gaston ; Decock, Gilbert ; De Groote, M.A. ; Delahaut, Jo ; Elias, Etienne ; Gentils, Vic ; Mara, Pol ; Peire, Luc ; Raveel, Roger ; Van Den Abeel, Jan ; Van Den Branden, Guy ; Van Hoeydonck, Paul ; Van Severen, Dan ; Verstockt, Mark ; Gaul, Winfred ; Tsoclis, Costas ; Swimberghe, Gilbert
boek